Combination of panax ginseng and ginkgo biloba extracts attenuate cerebral ischemia injury with modulation of NLRP3 inflammasome and CAMK4/CREB pathway - Zhao, Aimei; Liu, Nan; Jiang, Guozhi; Xu, Li; Yao, Mingjiang; Zhang, Yehao; Xue, Bingjie; Ma, Bo; Chang, Dennis; Feng, Yujing; Jiang, Yunyao; Liu, Jianxun; et al. (Frontiers in Pharmacology, 2022)
Stroke is a major cause of death and disability throughout the world. A combination of Panax Ginseng and Ginkgo biloba extracts (CGGE) is an effective treatment for nervous system diseases， but the neuroprotective mechanism underlying CGGE remains unclear. Both network analysis and experimental research were employed to explore the potential mechanism of CGGE in treating ischemic stroke (IS). Network analysis identified a total number of 133 potential targets for 34 active ingredients and 239 IS-related targets. What’s more, several processes that might involve the regulation of CGGE against IS were identified, including long-term potentiation, cAMP signaling pathway, neurotrophin signaling pathway, and Nod-like receptor signaling pathway. Our studies in animal models suggested that CGGE could reduce inflammatory response by inhibiting the activity of Nod-like receptor, pyrin containing 3 (NLRP3) inflammasome, and maintain the balance of glutamate (Glu)/gamma-aminobutyric acid (GABA) via activating calmodulin-dependent protein kinase type Ⅳ (CAMK4)/cyclic AMP-responsive element-binding protein (CREB) pathway. These findings indicated the neuroprotective effects of CGGE, possibly improving neuroinflammation and excitotoxicity by regulating the NLRP3 inflammasome and CAMK4/CREB pathway.